PELATIHAN PENGELOLAAN OBAT-OBATAN "DAGUSIBU" DI PONDOK PESANTREN RAUDLATUL MUSTOFA DUSUN PUNDENSARI TULUNGAGUNG - Gusti Noorrizka Veronika Achmad; I Nyoman Widjaja; Gesnita Nugraheny; Arie Sulistyarini; Yuni Priyandani; Abdul Rahem; Umi Athiyah (Jurnal Bakti untuk Negeri, 2025)
The DAGUSIBU (Obtain, Use, Store, and Dispose) training program on drug management was conducted at Pondok Pesantren Tulung Agung to improve the knowledge and skills of drug handlers and health workers. This study employed a pre–post test design with an intervention consisting of DAGUSIBU training involving 120 participants. Knowledge was assessed using written tests administered before and after the training, and data were analyzed statistically. The results demonstrated a significant improvement (p < 0.05) in participants’ knowledge scores, increasing from an average of 38.67 before training to 75.25 after training. These findings indicate that DAGUSIBU training is effective in enhancing drug management knowledge. This training model has the potential to be applied in Islamic boarding schools and other boarding-based educational institutions to improve the quality of drug management sustainably.